Strategi Kementerian Dalam Negeri (Kemendagri) di Balik Rendahnya Realisasi Anggaran Pemerintahan dan Belanja Daerah (APBD) - Rifki, M Saidi; Hutabarat, Frisca Natalia (Ministry of Home Affairs, 2023)
The Ministry of Home Affairs (MoHA), through the Directorate General of Regional Financial Management, created several strategies through several policies to accelerate regional spending. However, the strategies did not increase the realization of the Regional Budget (APBD). Therefore, this study aimed to analyze the strategy implemented by the Ministry of Home Affairs and why these strategies did not significantly impact the absorption of APBD. This study used a descriptive qualitative method with library research. The study found that one of the strategies, the Memorandum of Understanding between several ministries/agencies for early procurement, has not been effective in alleviating the doubts of regional governments. One possible solution is to ensure that early procurement by regional governments coincides with the preparation of RKA SKPD, as per Presidential Regulation No. 16 of 2018. MoHA should also promote the use of Evidence-Based Policy (EBP) in regional financial management and encourage the establishment of the Regional Financial Management Laboratory Unit (UPTLPKD). Finally, MoHA should prioritize the development of infrastructure that was delayed due to the COVID-19 pandemic in 2020 and 2021.